PROSES PRODUKSI BERITA UTAMA SURAT KABAR JAWA POS - Mochammad Naufal; Ali Muchasan (LPPM IAI Hasanuddin Pare-Kediri, 2019)
Newspapers are the oldest mass media and have become the spearhead of history in the birth of journalism. A high level of credibility is still a newspaper's criterion, when compared to other media. The news production process becomes the spotlight in production before being presented on the main page of a newspaper. Jawa Pos newspaper is one of the oldest media companies in East Java with one of the largest circulation in Indonesia. This study aims to determine and understand how the production process of headlines in the Jawa Pos newspapers becomes ready-to-print news as well as what obstacles are faced during the process and how are the solutions. The assessment method used in this study is a descriptive qualitative approach. Based on the results of the research, it can be concluded that in producing headlines in a daily newspaper, a fairly mature process is needed from each responsible element on each page, especially the main page. With this research, it is hoped that it can add to the knowledge of communication science studies, especially journalistic concentration on matters related to the news production process in the press world. And can be used as a reference for communication science students.